Phonemic changes in the impaired verb in Arabic and Hebrew (Comparative study) - صفية وحيد; شهرة علي (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
For the early Arabic jurists, the concept of verb is based - in its foundation - on the change, transfer, deletion and moderation. And since language is a living creature that is born and evolves - and like other living things - it has a share of life and a share of death; Accordingly, the impaired verb of all kinds had a share in that development. It is worth noting here that knowledge of phonological developments is not a product of the modern era. Rather, we find that the ancient Arab linguists dealt with the phonemic changes that affect the impaired verb. Modern Arabic-language scholars did not go far from what the ancients expressed, but added to it a summary of what the modern phonological lesson reached. Thus, the ancients’ study of the patterns of phonological changes affecting the impaired verb moved from mere mental assumptions to Linguistic facts. In our research, we tried to shed light on the most important patterns of phonological changes that affect the impaired verb from the viewpoint of the ancient and modern Arab linguists, comparing that with the changes that happen to this verb in the Hebrew language, the sister of the Arabic language.